2016
DOI: 10.1155/2016/4857917
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Aspartate Aminotransferase to Alanine Aminotransferase Ratio with BNP Level and Cardiovascular Mortality in the General Population: The Yamagata Study 10-Year Follow-Up

Abstract: Background. Early identification of high risk subjects for cardiovascular disease in health check-up is still unmet medical need. Cardiovascular disease is characterized by the superior increase in aspartate aminotransferase (AST) to alanine aminotransferase (ALT). However, the association of AST/ALT ratio with brain natriuretic peptide (BNP) levels and cardiovascular mortality remains unclear in the general population. Methods and Results. This longitudinal cohort study included 3,494 Japanese subjects who pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 29 publications
2
94
1
Order By: Relevance
“…Yokoyama et al [26] recently concluded that an increased AST/ALT ratio positively correlates with NT-proBNP levels, yet their study was not specific for HFrEF patients.…”
Section: Discussionmentioning
confidence: 95%
“…Yokoyama et al [26] recently concluded that an increased AST/ALT ratio positively correlates with NT-proBNP levels, yet their study was not specific for HFrEF patients.…”
Section: Discussionmentioning
confidence: 95%
“…Cox proportional hazard regression models were used to investigate the prognostic value of TG/HDL-C on diabetes risk, and adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) were estimated to evaluate the risk of diabetes. According to the recommendation of the STROBE statement [15], we simultaneously showed the results from unadjusted, minimally adjusted analyses and those from fully adjusted analyses. Whether the covariances were adjusted determined by the following principle: when added to this model, changed the matched hazard ratio by at least 10% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Aminotransferase, including AST and ALT, is a well-known marker for liver injury. AST is in both the liver and myocardial tissue, but ALT is only in the liver [8]. The elevation of the AST/ALT ratio is due to induction by alcohol consumption and cardio-hepatic interaction [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…Aminotransferase is a well-known marker for liver injury and is composed of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). ALT is only located in the liver, but AST is in both the liver and myocardial tissue [8]. A more significant increase in AST characterizes the elevation of aminotransferase in CVD compared with ALT, which presented an increased AST/ALT ratio in patients with CVD [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation